Hypocalcemia in Jersey dairy cows - Pelegrini, Mariana Monteiro Boeng; Molinari, Pietra Viertel; Lopes, Izaú Cardoso; Gueretz, Juliano Santos; Peripolli, Vanessa; Moreira, Fabiana; Bianchi, Ivan; Santos, Betina Raquel Cunha dos; Schwegler, Elizabeth (Seven Editora, 2024)
Dairy cows of the Jersey breed have stood out in dairy farming for their high productive and reproductive potential and, naturally, face the great metabolic challenges inherent to production. Hypocalcemia is one of the main diseases in the transition period, and the Jersey breed has physiological characteristics that can increase the occurrence of this disease. Prevention strategies continue to be the best option in preventing the disease. DOI:https://doi.org/10.56238/sevened2024.007-066